Personality-based analysis of resilience and aggressive behaviour: A latent profile approach - Karol Konaszewski; Sebastian Binyamin Skalski-Bednarz; Janusz Surzykiewicz; Arkadiusz Urbanek; Maciej Karwowski (Studia z Teorii Wychowania)
Personality traits reflect patterns of thoughts, feelings and behaviour that are characteristic of people. A person who manifests an intensity of certain traits is expected to behave in a manner consistent with the behavioural repertoire accepted for those categories over time. Therefore, in our study, using latent profile analysis (in a person-centered approach), we proposed to replicate personality trait profiles in terms of tendencies toward certain aggressive behaviours and resilience abilities. The study involved 670 people aged 18-29. The study procedure consisted of filling out psychological questionnaires measuring resilience, aggressive behaviour and personality traits. We replicated three personality profiles. Those with the "resilient" profile scored low on neuroticism and relatively high on conscientiousness, agreeableness and extraversion, in contrast to those with the "overcontrolled" profile, who scored significantly higher on neuroticism and lower on the extraversion domain. The "resilient" profile was characterized by the highest levels of resilience and the lowest levels of aggression. In contrast, the "overcontrolled" profile was characterized by low levels of resilience and high levels of aggression. The "adaptive" profile was the most numerous, with average scores in all Big Five domains and average scores in resilience and aggression. Our study shows that generalizable personality profiles can be identified empirically, and that the unique constellation of traits that define an individual has important implications for a wide range of behaviours including aggressive behaviour and resilience.